Effects of digoxin in inhibiting ACE2 and SARS-CoV-2 binding for attenuating COVID-19 in human adipocytes - Ardiana, Meity; Suryawan, I Gde Rurus; Hermawan, Hanestya Oky; Putri, Primasitha Maharani Harsoyo; Rahma, Safira (Faculty of Medicine Universitas Indonesia, 2024)
BACKGROUND Angiotensin-converting enzyme 2 (ACE2) has a role in SARS-CoV-2 incidence, and digoxin is a competitive inhibitor of SARS-CoV-2-ACE2 binding. This study aimed to investigate the effects of digoxin on SARS-CoV-2-ACE2 binding, proinflammatory cytokines, and prothrombotic factors in adipocytes of patients with COVID-19. METHODS This in vitro study used adipocyte cultures, which were divided into negative control, positive control (SARS-CoV-2 S1 spike protein only), SARS-CoV-2 S1 spike protein with digoxin, and SARS-CoV-2 S1 spike protein with human recombinant soluble ACE2 (hrsACE2). Data were analyzed using one-way ANOVA and Pearson correlation. RESULTS SARS-CoV-2 significantly elevated ACE2 and increased interleukin (IL)-6, tumor necrosis factor-alpha (TNF-α), tissue factor (TF), and plasminogen activator inhibitor-1 (PAI-1) compared to the negative control group (p<0.001). No SARS-CoV-2-ACE2 binding was detected in SARS-CoV-2 with digoxin and hrsACE2 groups, compared to the positive control group (0 ng/ml versus 0 ng/ml versus 36.33 [1.58] ng/ml, p<0.001). Digoxin significantly decreased IL-6 (48.94 [1.80] ng/ml versus 90.93 [4.29] ng/ml; p<0.001), TNF-α (87.65 [6.88] ng/ml versus 307.95 [57.34] ng/ml; p<0.001), TF (5.33 [0.32] ng/ml versus 6.85 [0.22] ng/ml; p<0.001), and PAI-1 levels (2.92 [0.168] ng/ml versus 4.86 [0.11] ng/ml; p<0.001), compared to positive control group. ACE2 positively correlated with IL-6 (p = 0.004, r = 0.763) and TF (p = 0.004, r = 0.768) but was not correlated with IL-1β, TNF-α, and PAI-1 levels. CONCLUSIONS This study promoted digoxin therapy to prevent cytokine storm and thromboembolism by decreasing IL-6, TNF-α, TF, and PAI-1 in adipocyte cultured models at an early stage of COVID-19.